2013
DOI: 10.1016/j.tig.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of AUTS2 in neurodevelopment and human evolution

Abstract: The autism susceptibility candidate 2 (AUTS2) gene is associated with multiple neurological diseases, including autism, and has been implicated as an important gene in human-specific evolution. Recent functional analysis of this gene has revealed a potential role in neuronal development. Here, we review the literature regarding AUTS2, including its discovery, expression, association with autism and other neurological and non-neurological traits, implication in human evolution, function, regulation, and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 76 publications
1
127
0
1
Order By: Relevance
“…Although there was no overlap between methylation of individual CpGs across all 4 NNNS outcomes, there was significant overlap at the gene level, suggesting that epigenetic patterning of these critical genes in different regions may influence multiple NNNS outcomes in a coordinated fashion. These overlapping genes included AUTS2, which is involved in neuronal development and linked to neurodevelopmental disorders, 50 and PCDHA, which traditionally localizes to synaptic junctions and is involved in neurogenesis, and is also implicated in neurodevelopmental disorders such as autism. 51 These genes were involved with molecular pathways involving cellular adhesion and nervous system development.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no overlap between methylation of individual CpGs across all 4 NNNS outcomes, there was significant overlap at the gene level, suggesting that epigenetic patterning of these critical genes in different regions may influence multiple NNNS outcomes in a coordinated fashion. These overlapping genes included AUTS2, which is involved in neuronal development and linked to neurodevelopmental disorders, 50 and PCDHA, which traditionally localizes to synaptic junctions and is involved in neurogenesis, and is also implicated in neurodevelopmental disorders such as autism. 51 These genes were involved with molecular pathways involving cellular adhesion and nervous system development.…”
Section: Discussionmentioning
confidence: 99%
“…AUTS2 expression in the brain has been confirmed to be associated with the alcohol preference in mice (Schumann et al 2011), whereas downregulating the expression of the Drosophila AUTS2 homologue dAUTS2/tay gene reduced the alcohol sensitivity of Drosophila (Schumann et al 2011). AUTS2 expression was found to be significantly associated with nicotine dependence, cannabis dependence, and antisocial personality disorder, whereas these small-scale studies need to be confirmed by larger cohorts (Philibert et al 2007;Oksenberg and Ahituv 2013). Chen et al recently confirmed that AUTS2 gene expression in lymphoblastoid cell lines (LCL) was significantly reduced in 124 male patients with heroin dependence compared with 116 healthy male controls (Chen et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Reportedly, AUTS2 contributes to the differentiation of human embryonic stem cells into cardiomyocytes, as well as the following differentiation of cardiomyocytes into beating embryoid bodies. 23) AUTS2 is involved in the Notch signaling pathway, 24) which takes part in mammalian cardiac development and is related to human congenital heart defects like bicuspid aortic valve disease, ventricular septal defects, and calcification of the heart valves. Moreover, AUTS2 is a transcriptome signature of heart malformations, 10) and it is associated with supravalvular aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%